Employee engagement among managerial in Lembaga Tabung Haji / Fatin Haamidah Mazlan - Mazlan, Fatin Haamidah (Faculty of Business and Management, 2018)
Public organization is non-profit institution and their focus is to provide efficient services for society rather for an individual. Public organizations often confront with high demand from society to deliver efficient services at low costs. Employees working in public organization must have engage with their work to ensure customers satisfy with their work then can increase organization productivity and performance. Employee engagement has become important variable to study because it can effect organization success. The objectives of this research is to determine and investigate which factors that can influence employee engagement among managerial level in Lembaga Tabung Haji, Kuala Lumpur. Convenience sampling techniques and personally administered questionnaires were used in this study. 193 questionnaires was collected from 273 and it was achieved 71% of response rate in this research. The data collected was evaluated through SPSS Version 22 software. Based on the result of regression analysis, there are two independent variable in this study were accepted and have positive relationship with employee engagement. However, change management and stress free environment are not significant towards employee engagement. Thus, career growth opportunities was the most influential variable towards employee engagement among managerial level in Lembaga Tabung Haji Headquarter.